Personnel management cases in developing countries - Cojeen, Robert H. (Ann Arbor : Program in International Business, University of Michigan, 1968)
This book is a collection of personnel management cases representing the work of different authors, both Nigerians and expatriates. The cases may be used in various ways as assignments for oral discussion, role playing, or written reports.
Includes bibliographical references p. 133-136.
hza 20/07/2018
Loans
Keywords: Personnel management; Developing countries